A Case Report on Ofloxacin Induced Maculopapular Rash - S, Sradha; Parween, Harsha; Eranhikkuth, Ameera Binth Musthafa; Rajesh, Amulya Diya Malammal; Thazhath, Ayisha Thacharupadikkal; Meachoth, Fathima Farsha; Chandrasekhar, Dilip; Keerthana, Sai (Indian Journal of Pharmacy Practice)
To report a case of maculopapular rashes secondary to the use of ofloxacin. A 23-year-old female was presented with maculopapular rashes throughout the body along with a reddish eye. The causality of the Adverse Drug Reaction (ADR) was assessed using the WHO UMC causality scale, and ADR was found to be probable. Ofloxacin was withdrawn and the patient was conservatively managed. By monitoring this occurrence, we were able to determine the correlation between ofloxacin and maculopapular rash. It was discovered that prompt offending agent withdrawal and supportive medication were beneficial.
Keywords: Case report; Adverse drug reaction; Ofloxacin; Maculopapular rash; WHO UMC Causality scale